Biogasoline synthesis via fluid catalytic cracking of waste cooking oil using treated eggshell - Syaiful Nizam, Hassan; Nurdin, Said; Zahira, Yaakob; Mohd Sabri, Mahmud (IOP Publishing, 2020)
This paper reports on preparation and characterization of eggshell for fluid catalytic cracking (FCC) reaction of waste cooking oil (WCO) to produce biogasoline. Hydrocarbon from condensate of gas emitted from a spherical flask reactor was agitated at 350, 400 and 450 resolution per minute (rpm) under 350, 400 and 450 oC reaction temperature by the one-factorat-a-time (OFAT) approach was analyzed by using a gas chromatography mass spectrometer (GC-MS). Acid compounds were also recorded. Earlier, the eggshell was ground, calcined at 900 oC for three hours and sieved into 250 – 425 m range of particle size before being analyzed using Fourier-transform-infrared-spectroscopy (FTIR) for calcium oxide content. About 30 wt% of biogasoline ranged from C4 to C12 of alkanes and alkenes was obtained from the 350-oC hydrocarbon condensate after 30, 45 and 60 min of which aromatic compounds increased with the reaction temperature. However, the biogasoline compounds decreased with the reaction temperature. More than 20 wt% was esters and free fatty acids of carbon number greater than 20 were also formed, respectively. Stirring speeds generally increased condensate yield but the increment does not have pattern due to various volatility of the content. The highest biogasoline yield through the FCC reaction was 4.5 wt% at 350 0C at 400 rpm stirring speed, and the product was found comparable with previous research and commercial gasoline.